An anonymous authentication scheme in data-link layer for VANETs. (2016) - Yao, Lin; Lin, Chi; Wu, Guowei; Jung, Taeyoung; Yim, Kangbin
In vehicular ad-hoc networks (VANETS), security and privacy are indispensable issues for guaranteeing the soundness of such a technology. In this paper, we focus on designing an efficient and lightweight anonymous authentication scheme. We propose a novel biometrics-based mutual authentication scheme in the data-link layer to protect a vehicle's privacy during its authentication phase. Our authentication scheme includes two phases, initialisation and anonymous authentication. During the initialisation phase, biometric encryption technique is applied to generate Bioscript. During the anonymous authentication phase, a new session key is generated to achieve the traffic confidentiality. Meanwhile, a newly temporary MAC address is negotiated to conceal the real MAC address. Security and privacy analysis show that our scheme can resist various attacks in the data-link layer. Furthermore, simulation results demonstrate that our scheme is a lightweight protocol.